Mechanistic understanding of fate and transport of selenium, arsenic, and sulfur in a pilot-scale constructed wetland treatment system designed for flue-gas desulfurization wastewater - Galkaduwa, Madhubhashini Buddhika (Kansas State University, 2015)
Constructed wetland treatment systems (CWTSs) are an alternative adaptation for flue-gas desulfurization (FGD) wastewater purification. A series of laboratory-based soil column studies mimicking a pilot-scale CWTS was carried out to evaluate the performance of the treatment system in detail. The main objectives of studies were to (1) understand the transport characteristics, retention capacity and transformation of selenium and other FGD constituents in the CWTS, (2) evaluate the effectiveness of soil treatments and influent flow rate on the performance of the CWTS, and (3) develop a mechanistic understanding of the CWTS performance through monitoring interrelationships of selenium (Se), arsenic (As), iron (Fe), and sulfur (S). Ferrihydrite (1% w/w), and labile organic carbon (OC) were used as soil treatments. Different influent flow rates, X (1.42 mL/hour), 2X, or 1/2X were used depending on the objectives of each study. Deoxygenated 1:1 mixture of FGD: raw water was the influent. It was delivered to the saturated columns with an upward flow. Effluent samples were collected continuously, and analyzed for constituents of concern. End of these experiments, soil from sectioned columns were used for total elemental analysis, sequential extraction procedure (SEP) for Se, and synchrotron-based X-ray spectroscopy analyses. Results indicated a complete Se retention by the columns. Boron, and fluorine partially retained whereas sodium, sulfur, and chlorine retention was weak, agreeing with field observations. Some of the initially-retained Se (~ 4 to 5%) was mobilized by changing redox conditions in the soil. Selenium fed with the wastewater accumulated in the bottom 1/3 (inlet) of the soil columns and was mainly sequestrated as stable forms revealed by SEP. Bulk-, and micro-XANES analyses suggested the retention mechanism of Se from the FGD wastewater was via the transformation of Se into reduced/stable forms [Se(IV), organic Se, and Se(0)]. Under wetland conditions, native soil As was mobilized by reductive dissolution of As associated minerals. However, the ferrihydrite amendment suppressed the native soil As mobility. Micro-XRF mapping integrated with As, and Fe-XANES suggested that the mechanism of native soil As retention was the sequestration of released As with newly precipitated secondary Fe minerals. A long-term study carried out with X, 1/2X flow rates, and OC source indicated enhanced S retention by the slow flow rate (1/2X), most likely due to the time dependency of biogenic S reduction. Further, bulk S-, As-, and Fe-XANES revealed that long submergence period and the slow flow rate increased the formation of reduced and/or biogenic S, realgar-like, and greigite-like species. These observations indicated that modified flow rates could have a significant impact on the long-term trace element (such as As) sequestration in the CWTS. Our studies provide useful information to improve the performance, and longevity of a full-scale CWTS for FGD wastewaters.
Keywords: CWTS; Selenium; Arsenic; Sulfur; XANESFGD; Agronomy (0285); Environmental Sciences (0768); Soil Sciences (0481)